Pengembangan Perangkat Lunak Simulasi PLTU Menggunakan Excel VBA untuk Aplikasi Rekayasa - Manggala, Agus; Yerizam, Yerizam; Effendy, Sahrul (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2025)
Coal-fired steam power plants (PLTU) remain essential in electricity generation, especially in countries with abundant coal resources. Thermodynamic modeling based on the Rankine cycle is crucial for both educational and design purposes, but commercial software is often costly and less accessible. This study develops a low-cost simulation tool using Microsoft Excel and VBA to model the Rankine cycle in PLTU systems. Users can input operating parameters, calculate thermodynamic properties using IAPWS-IF97 formulations, and evaluate system efficiency through energy balance analysis. The user-friendly interface features real-time efficiency graphs and energy flow diagrams. Validation results show deviations of less than 5% for key parameters, making this tool effective for engineering education, preliminary feasibility studies, and local research in thermal power generation.